Generation of a broadband xuv continuum in high-order-harmonic generation by spatially inhomogeneous fields - (:unkn) unknown (AMER PHYSICAL SOC, 2012)
We address an efficient scheme to generate a broadband extreme-ultraviolet (xuv) continuum from high-order harmonic generation emerging from the concept of plasmonic field enhancement in the vicinity of metallic nanostructures [Kim et al., Nature (London) 453, 757 (2008)]. Based on the numerical solution of a time-dependent Schrodinger equation, for moderate field intensities and depending on the inhomogeneity of the field, we are able to increase the plateau region roughly by a factor of two and generate a broadband xuv continuum. The underlying physics of the plasmon enhancement in harmonic generation is investigated in terms of the semiclassical trajectories of strong field-electron dynamics, and perfect consistency is found between quantum mechanical simulations. It is found that the field inhomogeneity plays a critical role in quantum path selection. After a critical value, we observe a systematic suppression in the long trajectories, suggesting the generation of a single isolated attosecond pulse. Finally, we investigate the dependence of cutoff position on the order of field inhomogeneity and find beta(2.3 -/+ 0.2) scaling.